The Concept Of Sumud, Resistance and Citizenship in Occupied Palestine: Critical Pedagogy and Muslim-Christian Living Together - Teeffelen, Toine van (Journal of Holy Land and Palestine Studies, 2025)
This article explores sumud (steadfastness) as a critical-pedagogical concept in Palestinian citizenship education in the occupied West Bank, supporting Muslim-Christian living together. Drawing on over a decade of educational practice and research by the Arab Educational Institute in Bethlehem, it examines interviews, grassroots experiences, and cultural expressions of sumud. The concept bridges moral thought and educational practice, linking resilience with national belonging. Despite the devastating Israeli war on Gaza, sumud persists through stories, symbols, and teaching methods, serving as both cultural expression and educational strategy. It aims to cultivate rooted, inclusive citizenship values amid ongoing occupation and adversity.